Propuesta para la elaboración de un manual de funciones, valuación de puestos por puntos y reglamento de admisión y empleo para el personal del campamento base de la empresa “Cnpc Chuanqing Drilling Engineering Company Limited”, ubicada en lago agrio, provincia de Sucumbíos - Bernal Paipa, Nansy Ernestina (2014)
Human talent today is an important tool for the modern management of large companies, which is why a successful full participation benefits the actions of the company. The project entitled "PROPOSAL FOR THE DEVELOPMENT OF A MANUAL OF FUNCTIONS, VALUATION OF POSTS FOR POINTS AND ADMISSIONS POLICY AND EMPLOYMENT FOR STAFF CAMP BASE COMPANY" CNPC Chuanqing DRILLING ENGINEERING COMPANY LIMITED ", LOCATED IN LAKE TART, PROVINCE SUCUMBIOS "whose main objective is to elaborate a manual functions, job evaluation points and rules for admission and employment for the base camp of the company" Chuanqing CNPC Drilling Engineering company Limited "located in Lago Agrio, Sucumbios Province ". In order to improve the management of human talent and Camp since that depends on its success. To meet the objective methods and techniques, which we have used the following; deductive method that helped determine the core problem, inductive part of the general to the particular, and that helped the analytical analysis of all the results of the investigation, interviewing techniques Mr. CNPC camp coordinator, the survey of 37 employees the camp. The analysis of the results the historical review was available, the existing organization in which maldistribution of charges is evident in the diagnostic interview results and applied survey are located, also was drawn to the operating functions which is shown responsibilities of each position to avoid duplication of functions, just as the valuation points that helped determine adjustments for three counts, whose slope is 3.68 update with this value the salary adjustment was performed with a factor was performed 3.66 valuation determined that allowed the new salaries. Subsequently I can determine in paragraph a) TITLE in which reference is made to the question asked, b) Summary in which the general objective, c) INTRODUCTION which allowed us to determine the structure of all the investigative work, d) REVIEW manifests LITERATURE which helped determine everything about the theoretical underpinnings, e) Materials and methods that allowed research analyzing everything f) rESULTS in which quantitative and qualitative results, g) DISCUSSION whole proposal is exposed to is proposed based on the results, h) conclusions that was obtained from all the work and i) Recommendations are the result of the findings, j) BIBLIOGRAPHY which are all k texts) ANNEXES where finds all the concerning the form of surveys and interview. Similarly the most important conclusions and recommendations were determined, employees know their functions entrusted to them, is not done in a technical way the admission process and employment and has not conducted a job evaluation to determine exactly their skills the position they are playing.